(untitled) (Herald of Journalism, 2016)
The author writes in his article about of the newspaper «Kazakh tili», released in the years 1919-1928 in Semey, so effused entire Kazakh land, and part of Mongolia, a thematic blog of the newspaper. In the «Kazakh tili» enough to those who are constantly raised by the authors diligently. For example, the problem of the Kazakh language, its implementation, training and educational matter, a matter of health, inequality of women in society, the issue of young people, the restoration of the rural economy, the movement of big industry, etc. The paper raised important issues such as the formation of literacy of the people in the impact of the national knowledge through a national school to give the young generation of national education. And also to deliver the news about the school, about science, and to promote progressive thinking to the people of the Kazakh educators.